2022
DOI: 10.3389/fpsyg.2022.911605
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Literacy on Entrepreneurial Intention: The Mediating Role of Saving Behavior

Abstract: This study explored the impact of financial literacy (financial awareness) on potential entrepreneurs' intent in Saudi Arabia. It also examined saving behavior as a mediator in the relationship between financial literacy and entrepreneurial intention. The study's data were collected by an online questionnaire sent to a sample of 270 potential entrepreneurs at Abqaiq Applied College, affiliated with King Faisal University. Data analysis was done using partial least squares structural equation modeling (PLS-SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Bindabel and Salim (2021) found positive relationships between investment, saving and orientation towards finance amongst Saudi university employees. Alshebami and Marri (2022) confirmed that saving behaviour could mediate financial literacy and entrepreneurial intention amongst potential Saudi entrepreneurs, namely, students demonstrating the importance of saving behaviour as a component of financial literacy in investment orientation. In another study by Saber (2020), it was reported that developing financial literacy is critical in Saudi Arabia because of the various radical changes made by the government in relation to the economy as a result of the global reduction in oil prices, which has negatively affected the Saudi budget.…”
Section: Introductionmentioning
confidence: 58%
“…Bindabel and Salim (2021) found positive relationships between investment, saving and orientation towards finance amongst Saudi university employees. Alshebami and Marri (2022) confirmed that saving behaviour could mediate financial literacy and entrepreneurial intention amongst potential Saudi entrepreneurs, namely, students demonstrating the importance of saving behaviour as a component of financial literacy in investment orientation. In another study by Saber (2020), it was reported that developing financial literacy is critical in Saudi Arabia because of the various radical changes made by the government in relation to the economy as a result of the global reduction in oil prices, which has negatively affected the Saudi budget.…”
Section: Introductionmentioning
confidence: 58%
“…Several studies (Alshebami & Al Marri, 2022;Ćumurović & Hyll, 2019) find an impact of financial knowledge on entrepreneurial intentions. Namely, Alshebami and Al Marri (2022) explore that financial knowledge affects EI through saving behavior.…”
Section: Financial Knowledgementioning
confidence: 99%
“…There have been very few studies in the context of Saudi Arabia that discuss the relationship between internal locus of control, entrepreneurial self-efficacy, and entrepreneurial resilience. The majority of prior research is concentrated on entrepreneurial education, institutions, entrepreneurial orientation, entrepreneurial intention, and similar concepts (Choukir et al, 2019;Aljarodi, 2020;Elnadi and Gheith, 2021;Abdelwahed, 2022;Alshebami and Marri, 2022). This study provides policymakers with the necessary strategies and policies to develop individuals' internal locus of control, entrepreneurial self-efficacy, and entrepreneurial resilience.…”
Section: Introductionmentioning
confidence: 99%